Current themes in molecular pediatrics: molecular medicine and its applications - Garavelli Livia; Superti-Furga Andrea (BMC, 2010)
Abstract We focus on themes that are derived from clinical practice and research in the field of genetic diseases of bone and inborn errors of metabolism but may be of more general interest as they indicate some trends in molecular medicine as related to pediatrics. Identifying the disease-causing mechanism brings about efficient therapeutic strategies and discovering the mutant genotype in the near future may become helpful for devising custom-built molecular responses. At the same time, the transition of therapy from the experimental phase to industrial application is difficult as there may be novel roles (and potentially conflicting interests) between physicians, patient organisations, governmental agencies and the pharmaceutical industry. Awareness of these potential conflicts may help in recognizing and dealing with these issues.